Much Ado About Food Safety Regulation In Nigeria - Ezirigwe, Jane (Journal of Sustainable Development Law and Policy, 2025)
About 1 in 10 people in the world fall sick after eating food contaminated through improper farming, processing, preservation and services. In Nigeria, more than 200,000 persons die of food poison annually, caused by contaminated foods. The cost of illnesses associated with foodborne diseases in Nigeria is estimated at US 3.6 billion per annum. Though there is poor data collection on foodborne outbreaks, evidence exists to show that these contribute to ill health and death in the country as well as reduce productivity and economic growth. Studies and existing facts reveal that law makers, enforcement officers, regulators, food handlers and even the consuming public do not take food safety very seriously. This article examines the varied cases of foodborne outbreaks in Nigeria with the aim to assess the role and ambit of food safety regulations in Nigeria. It seeks to determine whether the present regulatory framework permits adequate regulation of the informal sector that serves the majority of the Nigerian consumers. While observing various challenges that may be encountered by the regulators, it offers recommendations on issues that require legislative reforms and pragmatic approaches in tackling the regulatory challenges. It concludes that the intergovernmental and the multi-agency cooperation envisaged by the National Policy on Food Safety and its Implementation Strategy, 2014, will be better achieved if the definition of “food” in the food laws are extended, in line with best practices and current realities, to allow for comprehensive regulation and coordination of the food chain system.